Ethno-pharmacological Evaluation of Plants Resources of District Malakand, Pakistan - Ibrahim, Muhammad; Akhtar, Naveed; Khan, Sara; Bahadar, Haji (Ethnobotany Research and Applications, 2023)
Background. The present study was conducted to assess the ethno-pharmacological practices of medicinal plants by the local tribes of District Malakand, Pakistan. The people of the area are mostly poor and rely on local medicinal plants for their basic primary health care needs. During the survey it was perceived that the area is under extreme threat of overgrazing, deforestation and agricultural land expansion and needs urgent and proper ecological management to protect the important medicinal flora for future generations. Methods. The current Ethno-pharmacological study consists of frequent field visits and interviews with 200 local informers of the study area having different socio-economic and educational backgrounds. The information was collected from the indigenous people through interviews and semi- structured questionnaires .The data collected were analyzed with the help of quantitative indices such as Informant consensus factor (Fic) and Fidelity Level (FL%). The plants collected were identified with the help of flora of Pakistan and online plant databases. Results. A total of 130 medicinal plants belonging to 112 genera and 55 families were documented during this survey. The results showed that the plants collected during the survey were predominantly herbs (51%) followed by trees (27%), shrubs (19%) and climbers only (03%). The plants collected were mostly from Ruderal habitat (40%), followed by arable (36%), woodland (18%) and wetland (06%). On the basis of habit the plants collected were mostly Perennials (58%), followed by Annuals (39%) and Biennials only (03%). The majority of the plants used in the preparation of crude drugs were whole plant (33%), followed by leaves (25%), fruits (08%), roots (06%), shoots, flowers, barks, seeds (05%), gum and latex (03%) and bulb (02%) respectively. The highest Fic. values were recorded for cardiovascular and hypertensive diseases (1.0) followed by sore throat and narcotic diseases (0.80). The most important and extensively used species were Allium sativum L., Caralluma tuberculata N.E. Brown and Mentha spicata L. each with 100% FL value. This study showed that the area is gorgeous and rich in medicinal flora. The botanical name, local name, family name, flowering season, part used, and ethno-pharmacological uses of local medicinal plants were documented. Conclusion: During this survey it was observed that the research area District Malakand, Pakistan is rich in medicinal flora and most of the indigenous people are poor and depend on medicinal plants for their basic primary health care needs. The survey showed that medicinal plants were mostly used by the local people to cure of gastrointestinal, skin, mouth, genital, urinary, cold, cough and joint diseases. The study will provide a baseline for further ethno-botanical, ethno-medicinal, phytochemical and antimicrobial studies. Keywords: Medicinal plants, Ethno-pharmacological uses, Gastrointestinal diseases, Malakand, Pakistan.